(untitled) (Global Journal of Management and Business Research, 2017)
This study aims to evaluate the scientific principles underlying the training process, which takes place in five-star hotels where the training and qualifying of the administrative staff take place, along with the reflection of the quality of the training process regarding the quality of hotel services provided therein. The research also aims to clarify the concept of total quality management and the possibility of adopting it in the work of hotels. The study included training concept, its principles and elements, and the overall concept of quality and quality in training. As well as a field study of the reality of training in hotels through which data was collected and statistically analyzed and hypothesis were tested. The study gave the following recommendations: Paying attention to identifying training needs in a deliberate scientific approach, the preparation of training and educational programs about the quality and the total quality concepts, initiating practical procedures targeting the adoption of the quality management in hotels.